1999
DOI: 10.6028/jres.104.004
|View full text |Cite
|
Sign up to set email alerts
|

The NIST quantitative infrared database

Abstract: With the recent developments in Fourier transform infrared (FTIR) spectrometers it is becoming more feasible to place these instruments in field environments. As a result, there has been enormous increase in the use of FTIR techniques for a variety of qualitative and quantitative chemical measurements. These methods offer the possibility of fully automated real-time quantitation of many analytes; therefore FTIR has great potential as an analytical tool. Recently, the U.S. Environmental Protection Agency (U.S.E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 11 publications
8
119
0
Order By: Relevance
“…3). As PAN absorption bands do not approach saturation in these measurements, this error weighting method was considered to be more reliable in calculating such fits to Beer's law, rather than using the transmission weighting approach described by Chu et al (1999) for bands that approach saturation. Figure 1 shows peak absorbances measured for each of the five principal PAN bands plotted against determined PAN partial pressure.…”
Section: Resultsmentioning
confidence: 99%
“…3). As PAN absorption bands do not approach saturation in these measurements, this error weighting method was considered to be more reliable in calculating such fits to Beer's law, rather than using the transmission weighting approach described by Chu et al (1999) for bands that approach saturation. Figure 1 shows peak absorbances measured for each of the five principal PAN bands plotted against determined PAN partial pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The filter response function is plotted in Fig. 5 together with the SO 2 absorption coefficient measured by NIST (National Institute of Standards and Technology) (Chu et al, 1999).…”
Section: Quantifying Somentioning
confidence: 99%
“…This multiple burden method greatly improves the S/N ratio by using the high burden measurements to enhance the signal for the weak bands that might not exceed the noise floor in any given measurement (while down-weighting the nonlinear strong peaks), but also using the low burden measurements to bring out a better fidelity for the strong peaks by accounting for Beer's law saturation and detector nonlinearity effects. Chu et al 51 and Sharpe et al 52 have demonstrated the advantages of this method compared to a simple linear absorbance data fit at each wavelength bin, since the raw data also have a weighting factor to account for nonlinearity mechanisms. In this method the residual fit vector is, moreover, carefully analyzed since any chemical impurities, including the uncommon ones, readily manifest themselves in the fit residual.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative near-infrared cross-sections were determined using a slight variant of the method of Chu et al 50 and Sharpe et al 51 In this method, a series of Fourier transform IR measurements is made, each corresponding to a different mixing ratio of the pure analyte vapor in a stream of ultra-high purity (UHP) nitrogen gas. After the measurements, a composite absorption spectrum A(λ) is generated from the individual spectrum; the individual (298.1 K) measurements cover a large range (~2 orders of magnitude) of analyte burdens, each burden pressurized with N 2 to one atmosphere.…”
Section: Methodsmentioning
confidence: 99%